A Study on Customer Satisfaction across Information Search Behavior Typology - Wahyuningsih, Wahyuningsih; Tanamal, Johnny (Gadjah Mada International Journal of Business, 2008)
This study investigates customer satisfaction based on a typology of consumer search behavior. The findings demonstrate that the type of consumer as defined by whether and how they search for information (passive, rational-active, and relational-dependent) has different level of satisfaction. Rational-active and relational-dependent consumers are found to be the dominant consumer types who actively search for information before purchasing a product and thus perceive a higher level of satisfaction than do passive consumers. The identification of satisfaction within each type of consumer provides a reason for customers to repurchase the same product, or recommend it to other people. As a result, companies will be able to achieve an increase in profitability. Recommendations for companies and future research directions are presented.